Integrin α1β1 protects against signs of post-traumatic osteoarthritis in the female murine knee partially via regulation of epidermal growth factor receptor signalling. Issue 10 (October 2016) - Shin, S.Y.; Pozzi, A.; Boyd, S.K.; Clark, A.L.
Summary: Objective: To investigate the role of integrin α1β1 in the progression of post-traumatic osteoarthritis (PTOA), and elucidate the contribution of epidermal growth factor receptor (EGFR) signalling to the mechanism by which integrin α1β1 might control PTOA. We hypothesised that integrin α1β1 plays a protective role in the course of PTOA and that the effect of PTOA (e.g., synovitis, loss of cartilage and growth of osteophytes) would be exacerbated in mice lacking integrin α1β1 at every time point post destabilisation of medial meniscus (DMM). Methods: DMM or sham surgery was performed on integrin α1-null and wild type (WT) mice and the progression of PTOA analysed at 2, 4, 8 and 12 weeks post-surgery (PS) using micro-computed tomography (microCT), histology, and immunohistochemistry. In addition, the effects of EGFR blockade were examined by treating the mice with the EGFR inhibitor erlotinib. Results: Integrin α1-null female, but not male, mice showed earlier cartilage degradation post DMM surgery compared to WT controls. Furthermore, erlotinib treatment resulted in significantly less cartilage damage in integrin α1-null but not WT mice. Independent of genotype, erlotinib treatment significantly mitigated the effects of PTOA on many tissues of female mice including meniscal and fabella bone volume, subchondral bone thickness and density and cartilage degradation. In contrast, reduced EGFR signalling had little effect on signs of PTOA in male mice. Conclusion: Integrin α1β1 protects against PTOA-induced cartilage degradation in female mice partially via the reduction of EGFR signalling. Furthermore, reduction of EGFR signalling protects against the development of PTOA in female, but not male mice.